2019
DOI: 10.48550/arxiv.1911.00783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stealthy Hardware Trojan Exploiting the Architectural Vulnerability of Deep Learning Architectures: Input Interception Attack (IIA)

Abstract: Deep learning architectures (DLA) have shown impressive performance in computer vision, natural language processing and so on. Many DLA make use of cloud computing to achieve classification due to the high computation and memory requirements. Privacy and latency concerns resulting from cloud computing has inspired the deployment of DLA on embedded hardware accelerators. To achieve short time-to-market and have access to global experts, state-of-the-art techniques of DLA deployment on hardware accelerators are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Over time, research in the field of hardware-based sidechannel attacks have shown that hardware trojans [21], [35] can degrade the performance of DNN hardware accelerators while remaining extremely stealthy and difficult to detect. In the works by Tolulope et al and Zhao et al, hardware trojans have been used to attack DNN accelerators by analysing the memory data patterns [22], [23]. Recently, a work by Kim et al has shown that DNN performance is adversely affected by frequent accesses of the DRAM memory storing the DNN parameters, which cause bit-flipping [36].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, research in the field of hardware-based sidechannel attacks have shown that hardware trojans [21], [35] can degrade the performance of DNN hardware accelerators while remaining extremely stealthy and difficult to detect. In the works by Tolulope et al and Zhao et al, hardware trojans have been used to attack DNN accelerators by analysing the memory data patterns [22], [23]. Recently, a work by Kim et al has shown that DNN performance is adversely affected by frequent accesses of the DRAM memory storing the DNN parameters, which cause bit-flipping [36].…”
Section: Related Workmentioning
confidence: 99%
“…These works inform that hardware optimization strategies, used for reducing energy consumption, can be used effectively to address the software vulnerabilities in DNNs, specifically adversarial attacks. Other works have shown that hardware attacks can be made on DNN accelerators to cause them to malfunction resulting in serious performance degradation [21], [22], [23]. These works exploit the structural vulnerabilities of the hardware accelerator such as the microarchitecture and memory access patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the specific computation pattern of CNN, cloud computing have been employed to perform classification of deep learning models but this raises concerns of privacy [4]- [16], security [17] and latency. General-purpose processors are also not efficient for CNN implementation and can hardly meet the performance requirement [18].…”
Section: Introductionmentioning
confidence: 99%
“…Convolution Neural Networks (CNN) models have achieved significant success in machine learning and have found adoption in many fields [1]. CNNs are specially successful in computer vision [2] .…”
Section: Introductionmentioning
confidence: 99%